Recurrent Stroke in Minor Ischemic Stroke or Transient Ischemic Attack With Metabolic Syndrome and/or Diabetes Mellitus. Issue 6 (9th June 2017) - Chen, Weiqi; Pan, Yuesong; Jing, Jing; Zhao, Xingquan; Liu, Liping; Meng, Xia; Wang, Yilong; Wang, Yongjun; ,
Abstract : Background: We aimed to determine the risk conferred by metabolic syndrome (METS) and diabetes mellitus (DM) to recurrent stroke in patients with minor ischemic stroke or transient ischemic attack from the CHANCE (Clopidogrel in High‐risk patients with Acute Non‐disabling Cerebrovascular Events) trial. Methods and Results: In total, 3044 patients were included. Patients were stratified into 4 groups: neither, METS only, DM only, or both. METS was defined using the Chinese Diabetes Society (CDS) and International Diabetes Foundation (IDF) definitions. The primary outcome was new stroke (including ischemic and hemorrhagic) at 90 days. A multivariable Cox regression model was used to assess the relationship of METS and DM status to the risk of recurrent stroke adjusted for potential covariates. Using the CDS criteria of METS, 53.2%, 17.2%, 19.8%, and 9.8% of patients were diagnosed as neither, METS only, DM only, and both, respectively. After 90 days of follow‐up, there were 299 new strokes (293 ischemic, 6 hemorrhagic). Patients with DM only (16.1% versus 6.8%; adjusted hazard ratio 2.50, 95% CI 1.89–3.39) and both (17.1% versus 6.8%; adjusted hazard ratio 2.76, 95% CI 1.98–3.86) had significantly increased rates of recurrent stroke. No interaction effect of antiplatelet therapy by different METS or DM status for the risk of recurrent stroke ( P =0.82 for interaction in the fully adjusted model of CDS) was observed. Using the METS (IDF) criteria demonstrated similar results. Conclusions: Concurrent METS and DM was associated with an increased risk of recurrent stroke in patients with minor stroke and transient ischemic attack.